The impact of tumor burden score on prognosis in patients after radical resection of hepatocellular carcinoma: a single-center retrospective study - Huang, Junzhang; Zhou, Ying; Wei, Suosu; Tang, Yuntian; Zhang, Qiuhuan; Tang, Yi; Huang, Wei; Mo, Chongde (Frontiers in Oncology, 2024)
PurposeThis study examines the relationship between tumor burden score (TBS) and survival and recurrence following radical resection of hepatocellular carcinoma through a cohort study conducted in the Guangxi population of China.MethodsThis cohort study eventually recruited 576 HCC patients undergoing radical resection of HCC in the People’s Hospital of Guangxi Zhuang Autonomous Region during 2013–2022. After determining the best threshold TBS, all cases were grouped to evaluate the relationship between TBS versus overall survival (OS) and cumulative recurrence. Using X-Tile software, the best threshold TBS to judge patient prognostic outcome following radical resection of HCC was 10.77.ResultsKaplan–Meier curve analysis revealed that patients with high TBS showed considerably decreased OS relative to the control group, accompanied by an increased recurrence rate. According to multivariate Cox proportional regression, the patients with high TBS were associated with poorer OS (HR = 2.56, 95% CI 1.64–3.99, P < 0.001) and recurrence-free survival (RFS) (HR = 1.55, 95% CI 1.02–2.35, P < 0.001).ConclusionIn patients undergoing radical resection for HCC, higher TBS was significantly related to shorter OS and RFS.